2018
DOI: 10.1002/mnfr.201800658
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Increase Mucin Expression in Experimental Necrotizing Enterocolitis

Abstract: Scope Necrotizing enterocolitis (NEC) is a leading cause of morbidity and death in preterm infants, occurring more often in formula‐fed than breastfed infants. Studies in both rats and humans show that human milk oligosaccharides (HMOs) lower the incidence of NEC, but the mechanism underlying such protection is currently unclear. Methods and Results By extracting HMOs from pooled human breastmilk, the impact of HMOs on the intestinal mucin levels in a murine model of NEC are investigated. To confirm the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 54 publications
7
117
1
Order By: Relevance
“…Pooled mixtures of hMOs isolated from mother milk have been reported to support the intestine barrier function by increasing mucin expression . Here, we studied the modulatory effects of individual commonly present hMOs in mother milk, i.e., 2′‐FL, 3‐FL, and its acid hydrolysis product LNT2 on expression of goblet cell secretory related genes MUC2 , TFF3 , and RETNLB , and the Golgi‐sulfotransferase genes CHST5 and GAL3ST2 in goblet cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled mixtures of hMOs isolated from mother milk have been reported to support the intestine barrier function by increasing mucin expression . Here, we studied the modulatory effects of individual commonly present hMOs in mother milk, i.e., 2′‐FL, 3‐FL, and its acid hydrolysis product LNT2 on expression of goblet cell secretory related genes MUC2 , TFF3 , and RETNLB , and the Golgi‐sulfotransferase genes CHST5 and GAL3ST2 in goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, gut barrier function, is provided by tightly connected epithelial cells and mucus. hMOs are known to enhance epithelial barrier, but the relative effects of individual oligosaccharides on stimulate mucus function have not been studied yet. HMOs are also subject to modifications during passage through the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al developed neonatal intestinal organoid cultures derived from normal ileal biopsies from preterm infants undergoing laparotomy to resect NEC structures. 23 In this study, we demonstrated that treatment of human neonatal intestinal organoids with HMOs led to increased crypt budding and increased mRNA expression of mucin (Muc2). This indicates a direct role of HMOs in increasing mucin expression in experimental NEC.…”
Section: Neonatal Intestinal Organoids As Ex Vivo Models Of Necmentioning
confidence: 82%
“…22 Wu et al have also used the human-derived mucus-secreting cell lines LS174T and Caco-2Bbe1 to validate a direct role for human milk oligosaccharides (HMOs) in increasing mucin expression, as HMOs protect the neonatal intestine during experimental NEC through upregulation of mucin. 23 Taken together, in vitro models of intestinal epithelial injury are advantageous as they allow us to observe cell proliferation, apoptosis, and gene expression among other factors. These in vitro models have the advantage of overcoming the difficulty in identifying cellular and molecular contributors to disease and to independently modifying them in the whole-animal in vivo models.…”
Section: Intestinal Epithelial Cells For Studying Necmentioning
confidence: 99%
See 1 more Smart Citation